Bioenergijska priprava v športu – optimizacija danih sposobnosti - Mitić, Rok (Šport (Ljubljana), 2021)
The model of bioenergy conditioning in sports is a new and innovative concept, which can (together with expertly guided process of training) cover a wide area: from training or competition conditioning, faster regeneration after exertion, raising the immune system, improving mental state and overcoming stress, injury prevention to faster regeneration after injury. Bioenergy conditioning is based on ancient knowledge about the existence of life energy, modern scientific recognition of so-called biofield, a modern approach to energy therapy, as well as biotherapists’ years of experience working with athletes. The article describes basic concepts of bioenergy approach, potential operational mechanisms, the main areas of impact on the human organism, effects of bioenergy therapy on athletes, review of biofield impact on people’s health and examples from authors’ experience. It is based on more than 15 years of author’s experience in the field of energy healing and recognition of modern science in this field, which potentially opens the door to a new way of viewing life, health, as well as athlete’s conditioning.
Keywords: ability optimisation; bioenergija; bioenergy; bioenergy conditioning in sport; biofield; biopolje; bioterapija; biotherapy; optimizacija sposobnosti; sport; šport; športna priprava; športniki